2020
DOI: 10.1002/acp.3645
|View full text |Cite
|
Sign up to set email alerts
|

Eyewitness descriptions without memory: The (f)utility of describing faces

Abstract: Eyewitness descriptions provide critical information for the police and other agencies to use during investigations. While researchers have typically considered the impact of memory, little consideration has been given to the utility of facial descriptions themselves, without the additional memory demands. In Experiment 1, participants described face images to their partners, who were then required to select these faces from photographic lineups. Performance was error-prone when the same image appeared in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Prior work in this area shows above‐chance identification performance based on verbal descriptions (Fallshore & Schooler, 1995 ; Kramer & Gous, 2020 ). Study 1 improved understanding of face communication by showing that difficulties in describing faces for identification purposes are not ameliorated by allowing naturalistic communication.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Prior work in this area shows above‐chance identification performance based on verbal descriptions (Fallshore & Schooler, 1995 ; Kramer & Gous, 2020 ). Study 1 improved understanding of face communication by showing that difficulties in describing faces for identification purposes are not ameliorated by allowing naturalistic communication.…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, this is the first set of studies to explore how individual differences in face perception relate to face communication. Prior work has focused on the accuracy of face communication (Fallshore & Schooler, 1995 ; Kramer & Gous, 2020 ). Here, we found that face identification skill contributed to variance in face communication performance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations